2014
DOI: 10.1007/s40620-014-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone may be an early predictor of low serum hemoglobin concentration in patients with not advanced stages of chronic kidney disease

Abstract: BackgroundParathyroid hormone (PTH) has been associated with anemia only in dialysis patients with severe hyperparathyroidism. Whether an association between PTH and hemoglobin also exists in patients with chronic kidney disease not on dialysis (CKD-patients) is still unclear. In this study we evaluated the association between PTH and hemoglobin in CKD-patients without severe secondary hyperparathyroidism.MethodsHospitalized patients and outpatients (N = 979) were retrospectively evaluated and categorized acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In this study, current outcomes suggest that vitamin D interventions significantly induce transferrin saturation and iron levels. Active vitamin D (1, 25(OH) D3) may have beneficial impacts on the levels of parathyroid hormone (PTH), through increase in the absorption rate of calcium and suppression in the release of PTH from parathyroid glands [60]. Previous studies have proposed that depletion of PTH secretion could be related to improved erythropoiesis by inducing erythropoietin and erythroid progenitor formation as well as decreased fibrosis of the bone marrow [29,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, current outcomes suggest that vitamin D interventions significantly induce transferrin saturation and iron levels. Active vitamin D (1, 25(OH) D3) may have beneficial impacts on the levels of parathyroid hormone (PTH), through increase in the absorption rate of calcium and suppression in the release of PTH from parathyroid glands [60]. Previous studies have proposed that depletion of PTH secretion could be related to improved erythropoiesis by inducing erythropoietin and erythroid progenitor formation as well as decreased fibrosis of the bone marrow [29,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Russo et al . found that PTH concentrations were significantly inversely associated with hemoglobin concentrations among non-dialysis CKD patients [30*]. Furthermore, a recent study assessing risk factors for hyporesponsiveness to ESAs found that elevated concentrations of PTH were associated with reduced odds of becoming responsive to ESAs [31].…”
Section: Other Calciotropic Hormones and Anemiamentioning
confidence: 99%
“…[5][6][7] Similarly, negative effects of very high serum levels of PTH on serum hemoglobin were observed in patients on dialysis. 8 In fact, improved serum concentration of hemoglobin, need for lower doses of erythropoietin stimulating agents and reduced fibrosis of bone marrow were attained after either better control of secondary hyperparathyroidism or parathyroidectomy. [9][10][11][12][13][14][15][16][17] The introduction of recombinant human erythropoietin (rhEPO) therapy for treatment of anemia of patients undergoing hemodialysis (HD) has led to a significant reduction in anemia.…”
Section: Introductionmentioning
confidence: 99%